The Use of Pigs as a Translational Model for Studying Neurodegenerative Diseases - Hoffe, Brendan; Holahan, Matthew R. (Frontiers in Physiology, 2019)
In recent years, the move to study neurodegenerative disease using larger animal models with brains that are more similar to humans has gained interest. While pigs have been used for various biomedical applications and research, it has only been recently that they have been used to study neurodegenerative diseases due to their neuroanatomically similar gyrencephalic brains and similar neurophysiological processes as seen in humans. This review focuses on the use of pigs in the study of Alzheimer’s disease (AD) and traumatic brain injury (TBI). AD is considered the most common neurodegenerative disease in elderly populations. Head impacts from falls are the most common form of injury in the elderly and recent literature has shown an association between repetitive head impacts and the development of AD. This review summarizes research into the pathological mechanisms underlying AD and TBI as well as the advantages and disadvantages of using pigs in the neuroscientific study of these disease processes. With the lack of successful therapeutics for neurodegenerative diseases, and an increasing elderly population, the use of pigs may provide a better translational model for understanding and treating these diseases.